Strontium isoscape of sub-Saharan Africa allows tracing origins of victims of the transatlantic slave trade - Wang, X; Bocksberger, G; Arandjelovic, M; Agbor, A; Angedakin, S; Aubert, F; Ayimisin, EA; Bailey, E; Barubiyo, D; Bessone, M; Bobe, R; Bonnet, M; et al. (Nature Research, 2024)
Strontium isotope (87Sr/86Sr) analysis with reference to strontium isotope landscapes (Sr isoscapes) allows reconstructing mobility and migration in archaeology, ecology, and forensics. However, despite the vast potential of research involving 87Sr/86Sr analysis particularly in Africa, Sr isoscapes remain unavailable for the largest parts of the continent. Here, we measure the 87Sr/86Sr ratios in 778 environmental samples from 24 African countries and combine this data with published data to model a bioavailable Sr isoscape for sub-Saharan Africa using random forest regression. We demonstrate the efficacy of this Sr isoscape, in combination with other lines of evidence, to trace the African roots of individuals from historic slavery contexts, particularly those with highly radiogenic 87Sr/86Sr ratios uncommon in the African Diaspora. Our study provides an extensive African 87Sr/86Sr dataset which includes scientifically marginalized regions of Africa, with significant implications for the archaeology of the transatlantic slave trade, wildlife ecology, conservation, and forensics.